Corrosion characteristics of Q690qE high-strength bridge steel in simulated coastal–industrial environment and its influence on mechanical and corrosion fatigue behaviors. (25th July 2022) - Cai, Jiaxing; Sun, Liyang; Ma, Hongchi; Li, Xiaogang
Highlights: Corrosion pits were more likely to form in the coastal–industrial environment with Cl - ions concentrating at the bottom of pits. The mechanical property and residual corrosion fatigue life of corroded Q690qE steel was significantly reduced with increase in pre-corrosion time. A prediction model for the residual corrosion fatigue life of corroded Q690qE steel was developed. The corrosion fatigue initiation mechanism of pre-corroded steel was proposed. Abstract: The corrosion behavior of Q690qE high-strength bridge steel in simulated coastal–industrial environment was investigated through accelerated corrosion, and the corrosion features under different corrosion times were characterized. The effect of pre-corrosion level on mechanical and corrosion fatigue behaviors was also studied by using pre-corroded fatigue samples. Results show that corrosion pits were more likely to form in this environment, with chloride ions concentrating at the bottom of the pits, resulting in significant loss of the mechanical property and corrosion fatigue life. The corrosion fatigue initiation mechanism was proposed, and a prediction model for the residual corrosion fatigue life of corroded Q690qE steel was developed.